Black Silicon Fabricated By Silver-Assisted Chemical Etching For Flexible Solar Cells - Omar, Halo Dalshad (2023)
Monocrystalline silicon (mono c-Si) dominates more than 90% of photovoltaic market due to increasing solar cell efficiencies, technology maturity and reducing technology cost. Currently, photovoltaic manufacturing uses solar cells with 180 μm thickness. To reduce the technology cost, one promising strategy is by reducing the c-Si wafer thickness below 100 μm, whereby the wafer becomes flexible. Furthermore, flexible c-Si introduces new features including flexibility, light weight and makes thin c-Si highly attractive for flexible solar cells. Most importantly, thin c-Si solar cells usually demonstrate higher open circuit voltage (Voc) due to the lower bulk recombination and more efficient electron-hole pair extraction. However, one big challenge of the thin c-Si is the insufficient light absorption due to the indirect bandgap of the c-Si. Additionally, planar c-Si exhibits a high broadband reflection of around 35% within 300-1100 nm wavelength region, which further reduces the light absorption in the c-Si. To improve the light absorption in the thin c-Si wafers, black silicon (b-Si) offers a great potential for solar cell application since it yields a superior broadband light absorption within 300-1100 nm wavelength region. This is attributed to refractive index (n) grading effect,